Inkjet Printing: Inkjet‐Printed and Deep‐UV‐Annealed YAlOx Dielectrics for High‐Performance IGZO Thin‐Film Transistors on Flexible Substrates (Adv. Electron. Mater. 6/2019). (6th June 2019) - Bolat, Sami; Fuchs, Peter; Knobelspies, Stefan; Temel, Ozgur; Sevilla, Galo Torres; Gilshtein, Evgeniia; Andres, Christian; Shorubalko, Ivan; Liu, Yujing; Tröster, Gerhard; Tiwari, Ayodhya N.; Romanyuk, Yaroslav E.
Abstract : Recent developments in inkjet printing have shown it to be a viable method for low‐cost and large‐area coating of oxide materials. In article1800843, S. Bolat et al. report the low‐temperature synthesis of yttrium aluminum oxide (YAlO x ) dielectric layers through a combination of inkjet printing of sol–gel precursors and heat‐assisted deep ultraviolet (DUV) annealing. Using this process, the post‐deposition annealing temperature required is reduced to a level compatible with sensitive polymer substrates.